COMPARITIVE STUDY OF DELAYED PRIMARY CLOSURE VERSUS PRIMARY CLOSURE OF SKIN IN CONTAMINATED AND DIRTY ABDOMINAL WOUNDS/ INCISION - BHADRAGOUDRA, JADESH; NARASANAGI, BASAVARAJ; VALLABHA, TEJASWINI; SINDAGIKAR, VIKRAM (International Journal of Clinical and Biomedical Research, 2016)
Background: It is still a matter of debate whether delayed primary closure (DPC) of contaminated abdominal incision reduces surgical site infection compared with primary closure (PC ). The rate of wound infection for dirty abdominal wound is approximately 40%, but the optimal method of wound closure remains controversial. Aims and objectives: To determine whether delayed primary skin closure of contaminated and dirty abdominal wounds reduces the rate of surgical site infection (SSI) compared with primary skin closure. Method: Patient diagnosed as acute peritonitis and posted for exploratory laparotomy during the period of October 1 2013 to September 1 2015 were included. The study was conducted at Shri B M Patil Medical College and Hospital, Bijapur. In this series a total of 100 patients were included and were divided in two groups. Each group had 50 patients. For primary closure group, wounds were closed with monofilament interrupted suture. For Delayed primary closure, skin and subcutaneous tissue are left open and packed with 10 % (betadine) povidone iodine soaked gauge, which was changed daily to prevent excessive collection of exudates. The outcome of wound was assessed on post - operative days. Result: In this entire series, wound infection developed after incision closure was 33% .The primary group had a higher rate of wound infection 54% and delayed primary closure was 12% (P<0.001) and longer length of hospital stay 19.4 days in primary closure group and 16.5 days in delayed primary closure group (P<0.002). Conclusion: Laparotomy wound complications are multifactorial, it depends on many factors. A strategy of DPC of dirty abdominal wound, clinically appears to decrease the rate of wound infection, when compared with PC without increasing the length hospital of stay.